Do it Right: Appropriate Ways for Teachers to Treat and React to Aggressive Children in Jordanian Kindergartens - Ebtesam Q. Rababah; Majedah F. Abu Alrub (Sultan Qaboos University, 2018)
This study explored the types and causes of aggression and the ways teachers treat and react to aggressive children in Jordanian kindergartens in the Irbid district. The sample consisted of the first 20 teachers who responded to the letter of participation sent to them.  Data on the causes and types of aggression and prevention strategies were collected by descriptive qualitative design, with semi-structured open-ended interviews, as well as observation of Jordanian kindergarten teachers. The results of the study revealed three themes: factors that shape aggression, sanctions rather than punishment and social learning and culture. Also, the results indicated that social learning through positive modelling was mostly needed to help aggressive and disruptive students and change their behaviour. In light of the results, further research utilizing quantitative and qualitative research methods to achieve broader understanding of aggression in pre-school settings is recommended.